PENGARUH PENDAPATAN ASLI DAERAH, DANA TRANSFER, LAIN-LAIN PENDAPATAN DAERAH YANG SAH TERHADAP BELANJA DAERAH (Studi pada Pemerintah Kabupaten/Kota di Provinsi Jawa Tengah Tahun 2017-2020) - Faizah Nikmatur Rohmah; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2023)
This study aims to determine the effect of Regional Tax, Regional Retribution, General Allocation Fund, Specific Allocation Fund, and Other Lawful Local Revenue on Regional Expenditure in District/City Governments in Central Java Province. Regional Expenditure has the role of running the government system, namely increasing the welfare of the community as a form of good governance..The population of this study are districts/cities in Central Java province. This study uses multiple linear regression analysis using data obtained from the Audited Regional Government Financial Statements (LKPD) in the form of Regional Revenue and Expenditure Budget Realization Reports (LRA APBD) which have been audited in Regencies and Cities in Central Java Province in 2017 -2020. The results of simultaneous research on Regional Tax, Regional Retribution, General Allocation Fund, Specific Allocation Fund, and Other Lawful Local Revenue have affect Regional Expenditures. The results of the study partially show that regional tax, general allocation fund, and specificl allocation fund have an effect on regional expendictures. Regional Retribution and Other Lawful Local Revenue do not affect  Regional Expenditure